Praktik Gadai Pohulo’o di Gorontalo dalam Perspektif Hukum Islam - Podungge, Rulyjanto (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
Muslim communities believe that compliance with the law is not only in the field of worship but also in the field of muamalah. Therefore, people want what they practice to be legal and in accordance with Islamic teachings. One of the problems whose legal status continues to be questioned is the issue of pawning which is carried out under customary law. There have been many explanations regarding this problem by religious leaders, but their answers have not been able to satisfy the community. The answers available so far tend to conclude that the practice is not allowed, the law is haram. It is undeniable that the explanation of this in fiqh books is indeed the case because the collateral in the pawn cannot be used by the pawnee, who in this case is a creditor. A creditor may not take advantage of the pledged goods for reasons of riba (usury). However, the practice of pawning, which is carried out according to custom, has become a tradition in the community and is carried out with the pleasure of the pawnbroker and pawnee, and this tradition has become a means to get out of trouble to cover one's life. This article explains the problem of the pawn tradition in Muslim society through a sociological approach in addition to the usuliyah syar'iyah approach